PERSEPSI MAHASISWA TENTANG PERLINDUNGAN SAKSI DAN KORBAN BERDASARKAN UNDANG-UNDANG NOMOR 31 TAHUN 2014 DI JURUSAN PIPS FKIP UNIVERSITAS RIAU - Rindy rinanda; Hambali '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :This research was almost the assumption that to be witness is very compleceted of evildoers crimes, while information given a witness needed to know a crime. The writer’s have given a guarantee of protection and safety to witnesses and the number is UU 31 of 2014. Students as the intellectual sued for to participate in assisting communities to provide support to the want to get statment in a crime.Students also forced to attend the wheels goverment according to values of Pancasilae specially sila number 2 and humanity fair and civilized always upholds justice for indonesian citizens. The purpose of this study was to determine students' perceptions about the protection of witnesses and victims based on UU No. 31 of 2014 in the Department of PIPS FKIP Riau University.This research was conducted at the Department of PIPS FKIP University of Riau in Pekanbaru. The Samples of this research is 62 people. Using proportional random samples. Technique analysis data from this study were obtained from questionnaires, observation and documentation. The Mechanical of data were analyzed descriptive quantitative, in processing of data obtained from a questionnaire distributed to respondents is presented in the form of a percentage, using the formula P = F / N x 100%. Based on the writer's observation that the perception of students in the field of protection of witnesses and victims based on number 31 of 2014 at the Department of PIPS FKIP Riau University is "good enough".Key Words: Perception Students, Protection, Witness and victims